Collaboration Between Humans and Robots in Organizations: A Macroergonomic, Emotional, and Spiritual Approach - Firescu, Violeta; Gaşpar, Mirabela-Luciana; Crucianu, Ioan; Rotariu, Eliade (Frontiers in Psychology, 2022)
The new managerial challenges are related to finding solutions for complex problems, inside some more and more complex management systems, in a continuously changing organizational context. Competitivity and progress imply a continuous positive change and the need to accept, respond and adapt to organization’s internal and external environments changes. This brief research report aims to point out the organizational ergonomics’ contribution to employees’ well-being through a systemic, emotional, and spiritual approach of man’s interaction with technology, systems, and organizational environment. The research methods used were the multidisciplinary bibliographic study and the interview. Three semi-structured interviews were taken to explore today’s challenges and new 4.0 technologies’ impact, especially robots, on company and on employees’ well-being and spiritual fulfilment. The novelty comes from the analysis of new technologies impact on the human factor from the spiritual point of view. Our main results have to do with the shaping of a model for human capital’s valorization and with suggesting a list for monitoring human capital valorization in the company. This paper’s main conclusion shows that the organizations’ management must be prepared to manage the conflict of the future, the conflict between humans and robots, by improving the employee’s abilities and adaptability to change and collaboration with robots.